Elucidating potential‐induced degradation in bifacial PERC silicon photovoltaic modules. (5th June 2018) - Luo, Wei; Hacke, Peter; Terwilliger, Kent; Liang, Tian Shen; Wang, Yan; Ramakrishna, Seeram; Aberle, Armin G.; Khoo, Yong Sheng
Abstract: This paper elucidates the behavior and underlying mechanism of potential‐induced degradation (PID) on the rear side of p‐type monocrystalline silicon bifacial passivated emitter and rear cell (PERC) photovoltaic modules. At 50°C, 30% relative humidity, and −1000 V bias to the solar cells with aluminium foil on the rear glass surface, the rear‐side performance of bifacial PERC modules at standard testing conditions degraded dramatically after 40 hours with a 40.4%, 36.2%, and 7.2% loss in maximum power ( P mpp ), short‐circuit current ( I sc ), and open‐circuit voltage ( V oc ), respectively. The front‐side standard testing condition performance, on the other hand, showed less degradation; P mpp, I sc, and V oc dropped by 12.0%, 5.2%, and 5.3%, respectively. However, negligible degradation was observed when the solar cells were positively biased. Based on I‐V characteristics, electroluminescence, external quantum efficiency measurements, and the effective minority‐carrier lifetime simulation, the efficiency loss is shown to be caused by the surface polarization effect; positive charges are attracted to the passivation/antireflection stack on the rear surface and reduce its field effect passivation performance. Extended PID testing to 100 hours showed an increase in device performances (relative to 40 hours) due to the formation of an inversion layer along the rear surface. In addition, replacing ethylene‐vinyl acetate copolymer with polyolefin elastomer films significantly slows down the progression of PID, whereas a glass/transparent backsheet design effectively protects the rear side of bifacial PERC modules from PID. Furthermore, PID on the rear side of bifacial PERC modules is fully recoverable, and light greatly promotes recovery of the observed PID. Abstract : At 50°C, 30% relative humidity and −1000 V bias to the solar cells with aluminium foil on the rear glass surface, the rear‐side performance of p‐type mono‐Si bifacial PERC modules at STC degraded dramatically after 40 hours with a 40.4%, 36.2%, and 7.2% loss in P mpp, I sc, and V oc, respectively. The PV efficiency loss is caused the surface polarization effect, where positive charges introduced by PID to the rear surface reduce the field effect passivation of the AlOx /SiNx stack.